Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia - Mohrig, Werner; Kauschke, Ellen; Broadley, Adam (Zootaxa, 2016)
The genus Pseudolycoriella Menzel & Mohrig, 1998 is distributed worldwide and especially species rich within the southern hemisphere. Within the Australasian region it is known from New Zealand (Mohrig & Jaschhof 1999; 5 species), New Caledonia (Köhler & Menzel 2013; 14 species) and Papua-New Guinea (Mohrig 2013; 22 species). Here we report the first records of the genus from Norfolk Island and Australia.